Exploring the implications of the use of Official Languages Act 12 of 2012 on the establishment of the indigenous language courts in the Vhembe District, Limpopo Province, South Africa - Choshi, Madumetja Kate (My University, 2016)
This study explored the implications of Act 12 of 2012 on the establishment of indigenous languages within the ambit of the Constitution of the Republic of South Africa’s Act 108 of 1996 on the use of English and Afrikaans Languages only in the Vhembe District criminal court proceedings. The establishment of the Indigenous Language Courts for the purpose of using indigenous languages, namely Tshivenda, Xitsonga and Sepedi as languages of court was the main objective of this study. This study investigated (a) whether present legally-recognised methods on the use of English and Afrikaans only in criminal court proceedings give effect to the right to a fair trial and (b) what are the implications of the Use of Official Languages Act on the use of English and Afrikaans only in the Vhembe District multilingual criminal courtrooms. This was accomplished through qualitative methods of data collection and analysis, namely in-depth personal interviews and textual analysis of the literature and case law review on the phenomenon under investigation. The interviews were conducted with samples of seven categories of participants, namely, the accused persons, the convicted persons, the court officials, court interpreters, the DJ & COND Directors, the PanSALB and one University Centre for African Languages i.e. UCT. Through both methods, it was revealed that the legally enforceable methods that prefer the use of English and Afrikaans as languages of the courts and court records over the accused’s indigenous language or their mother-tongue in the entire trial thereby negating their right to a fair trial, are the provisions of the legislation and the Constitution and their application thereof, as well as legal instructions and culture. It was further revealed that this Act implied the elimination of the use of English and Afrikaans and creates opportunity to the accused’s right to use his or her mother-tongue as one of the indigenous languages in the entire trial thereby affording the accused the right to a fair trial. The study found that the two theories as designed and implemented revealed problems on the ground and helped this research to conclude that these legally enforceable methods created the feeling of unfair treatment amongst the users of the indigenous languages in court. It suggested that the three identified indigenous languages be used as languages of court and of court record.
PhD (African Studies
Centre for African Studies
Keywords: Indigenous languages; Criminal courts; UCTD; Language of Court; Language of court record; The right to a fair trial; Vhembe District